2006
DOI: 10.1002/nbm.1077
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of a bimodal contrast agent on cellular functions and relaxometry

Abstract: The in vivo monitoring of cell survival and migration will be essential to the translation of cell-based therapies from the laboratory to clinical studies. The pre-labeling of cells with magnetic resonance imaging (MRI) contrast agents renders them visible in vivo for serial cellular imaging. However, little is known about the impact of the presence of these metal particles inside transplanted cells. The use of the bimodal contrast agent GRID made it possible to demonstrate by means of fluorescent microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 40 publications
(75 reference statements)
3
65
1
Order By: Relevance
“…Under these conditions, the resulting intracellular iron load is 626 pg/cell. This is significantly higher than reported in other studies using different cell types (9,25). In these studies murine hepatocytes were labeled with MPIOs and they generally contained iron levels of 100 pg.…”
Section: Discussionmentioning
confidence: 74%
“…Under these conditions, the resulting intracellular iron load is 626 pg/cell. This is significantly higher than reported in other studies using different cell types (9,25). In these studies murine hepatocytes were labeled with MPIOs and they generally contained iron levels of 100 pg.…”
Section: Discussionmentioning
confidence: 74%
“…Next, the vesicle suspension (1.5 mL) was mixed with the neutral MLs (1.5 mL), and the mixture was incubated, overnight, at 37 8C, followed by a second round of HGM purification to provide the MLs containing 3. 33 2) MLs with a fluorescent lipid conjugate in the inner lipid layer were produced by mixing 3 mL of sonicated vesicles (12 mg of lipids, of which 1 mol % consisted of b-BODIPY FL C 5 -HPC) with the magnetic fluid (0.3 mL) at room temperature (Fe 3 O 4 concentration of the stock solution: 114 mg mL À1 ), followed by dialysis (6 h) at 37 8C against TES buffer (5 mm, pH 7.0), with a buffer change every 2 h (Scheme 1 B). Under these conditions all phospholipid components are adsorbed as a single layer on to the magnetite surface.…”
Section: Discussionmentioning
confidence: 97%
“…Although 3T3 fibroblasts are known to be highly proliferative cells, this value greatly exceeds the timespan of 5-7 doublings found by Brekke et al, [33] who used A C H T U N G T R E N N U N G gadolinium rhodamine dextran structures to label Maudsley hippocampal cell clone 36 cells, or by Walczak et al, [15] who labelled C17.2 neural stem cells with Feridex. These findings might, however, be somewhat deceiving, because both studies also used fluorescence microscopy to monitor the fate of the internalised nanoparticles over time, but the quantum yield of the label, the amount of fluorophores per particle and the specific cell type used are all parameters that can influence the outcomes of these studies.…”
Section: A C H T U N G T R E N N U N G Internalisation Mdc Is a Compmentioning
confidence: 92%
“…In contrast to an expected signal enhancement, clusters of Gd-labelled cells were found to give rise to signal loss under both in vivo and in vitro conditions. 31,69,70 Explanations for this phenomenon include aspects regarding the local concentration of Gadolinium and the effect of compartmentalization of the Gd-based agents influencing the rate of exchange and the availability of free water protons. Capitalizing on the compartmentalization effect, Guenoun et al 71 proposed using the changing contrast behaviour of cells labelled with gadolinium liposomes as a read out method for assessing the functional status of injected cells (Figure 3).…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…They showed that at an identical Gd concentration, Gd incorporated inside the cell gave rise to signal loss while Gd released from non-viable cells resulted in signal gain which quickly dissipated. 31,71 Despite the fact that various studies showed limited or no adverse effects of the Gd-based labelling agents on the functionality of labelled cells at relevant labelling concentrations, 31,62,63,66,68,72 major concerns regarding the toxicity of the long-term presence of ionic Gd exist, 70,73,74 which may limit introduction of such agents into the clinic. Gadolinium contrast agents have been associated with the occurrence of nefrogenic systemic fibrosis in patients with impaired kidney functions, and Modo et al 74 reported on a negative effect on disease pathology of implanted neural stem cells labelled with the Gd-based contrast agent GRID (Gadolinium-Rhodamine Dextran) in a rat stroke model.…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%